Entre telas e lacunas: competências digitais entre os alunos da Educação de Jovens e Adultos - Silva, Natália da Rocha da (Universidade Federal de São Carlos, 2026)
This study investigates the development of digital competencies among students enrolled in Youth and Adult Education (Educação de Jovens e Adultos – EJA), focusing on individuals who did not complete elementary education during their regular school trajectory. The research is grounded in the understanding that the intensification of digitalization in contemporary society has increased the demand for competencies related to the use of Information and Communication Digital Technologies (ICDTs), thereby deepening inequalities historically associated with low levels of schooling and socioeconomic vulnerability. This is an applied field study with a descriptive design and a quantitative approach, conducted through a data survey. A total of 110 printed questionnaires with closed ended questions were administered to students from two public municipal schools located in the cities of Araraquara and São Carlos, São Paulo, Brazil. The analysis is informed by the Science, Technology and Society (STS) field, articulating the concepts of digital competence, digital exclusion, and Youth and Adult Education. The findings indicate that although internet access is widespread among participants, the development of digital competencies remains limited and uneven. The results highlight the centrality of smartphones as the main device used to access the internet, as well as the predominance of practices related to social media use and video consumption. In contrast, there is limited use of digital tools associated with information production, organization, work-related activities, and citizenship. Significant difficulties in the digital learning process were also identified, linked to both structural and educational factors, such as low educational attainment, limited income, lack of formative mediation, insecurity in dealing with technological changes, and fear of making mistakes or falling victim to digital fraud. Despite these barriers, most participants expressed a strong interest in learning more about digital technologies, indicating that digital exclusion in this context is not the result of a lack of motivation, but rather of insufficient access to continuous and contextualized learning opportunities. It is concluded that digital exclusion goes beyond the issue of access, encompassing limitations in the autonomous, critical, and meaningful use of digital technologies. The findings reinforce the need for integrated public policies that take into account the specificities of Youth and Adult Education, combining access, training, pedagogical mediation, and material conditions in order to promote socially situated digital inclusion.
Between screens and gaps: digital skills among students in Youth and Adult Education
Keywords: Competência digital; Exclusão digital; Educação de Jovens e Adultos; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes